University Initiatives in Climate Change Mitigation and Adaptation (Springer, 2018)
This book focuses on the role of higher education institutions in addressing climate change mitigation and adaptation challenges, contributing to the development of this fast-growing field. Further, it includes the results of empirical research and offers ideas regarding on-going and future research initiatives. The contributions also • showcase the research and projects on issues pertaining to climate change at universities from across the globe; • document and promote ideas and experiences acquired in the execution of research projects, especially successful initiatives and best practices; and • introduce methodological approaches and projects that offer a better understanding of climate change across society and economic sectors. The book is structured around two parts: lessons learned from climate change research, education, studies and projects. Each part focuses on mitigation and adaptation respectively, with many responses of the two modalities overlapping. This book is a valuable resource for researchers and practitioners in the fields of environment, human geography, business and economics, as well as academics and students, as it presents education, communication and awareness-raising projects on matters related to climate change at universities in both industrialised and developing countries, often in cooperation with government bodies, NGOs and other stakeholders.
Keywords: Climate Change Communication; Sustainable Development; Environmental Management; Climate Change Education; Climate Change Research; climate change; Climate change management